Um estudo sobre os reflexos das ações da Ditadura Militar através do Jornal o Estado de Mato Grosso (1964-1974) - Meira, Leonice Maria (2011)
The Latin American political stage during the latter half of the twentieth century was marked by the unleashing of coups and the military rise to power. In Brazil "The Military Coup" took place in 1964 when the military rose to power and broke down the constitutional government of Joao Goulart. The object of this research is aimed for the news about the consequences of the actions of the military dictatorship in Mato Grosso, which were presented by the daily "O Estado de Mato Grosso." To carry out this study, we chose this newspaper, in order, in addition to being a popular mean of communication; it allows us to observe the several political changes that occurred over this period, which was very disturbed in Brazilian politics as Mato Grosso policy. We chose this medium of communication because it is a newspaper with the greatest longevity at that time, thus allowing a temporal sequence feasible. The development of this research was accomplished through the survey and critical analysis of documental supplies from the collections: The development of this research was conducted through a survey and critical analysis of documentary sources of the collections: Public Archive of Mato Grosso – PALM, and the Center for Documentation and Information of Regional History - CDIRH. The methodology used in this study was based on the New Political History. Thus, we intend with this research to carry out thoughts on the transition from democracy to military dictatorship by examining the relationship between the government of Mato Grosso and the military government in the spatiality of Mato Grosso during the time frame from 1964 to 1974, because we understand that historiography of Mato Grosso can be enhanced with searches in this perspective, thus enabling comprehend how these actions were developed and resulted several changes in the state after the implementation of military regime.